2012
DOI: 10.1155/2012/373219
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activities of Kushen: Literature Review

Abstract: To discover and develop novel natural compounds with therapeutic selectivity or that can preferentially kill cancer cells without significant toxicity to normal cells is an important area in cancer chemotherapy. Kushen, the dried roots of Sophora flavescens Aiton, has a long history of use in traditional Chinese medicine to treat inflammatory diseases and cancer. Kushen alkaloids (KS-As) and kushen flavonoids (KS-Fs) are well-characterized components in kushen. KS-As containing oxymatrine, matrine, and total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 40 publications
1
84
0
Order By: Relevance
“…These reports include using CKI to treat gastric cancer, liver cancer, lung cancer, breast cancer, ovarian cancer, colorectal cancer and other cancer types [11] . Recently, the mechanisms of CKI used as anti-cancer therapy were investigated.…”
Section: Studies On Compound Kushen Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports include using CKI to treat gastric cancer, liver cancer, lung cancer, breast cancer, ovarian cancer, colorectal cancer and other cancer types [11] . Recently, the mechanisms of CKI used as anti-cancer therapy were investigated.…”
Section: Studies On Compound Kushen Injectionmentioning
confidence: 99%
“…In addition, it has synergistic and attenuation actions with anti-tumor agents in H22 and S180 cancer cells. The anti-tumor mechanisms of CKI may include: (1) increased protein expression of p16; (2) reduced unmethylated state of the p16 gene; (3) inhibited VEGF and MVD expression in neoplastic tissues; (4) decreased microvessel density [11,27,28] . Zhou et al [28] investigated the effects of CKI on gastric immunity and oxidantantioxidant status during N-methyl-N'-nitro-N-nitrosoguanidine (MNNG)-induced gastric carcinogenesis.…”
Section: Studies On Compound Kushen Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) As a widely distributed and effective herbal medicine, it severed as a cure for asthma, sores, gastrointestinal hemorrhage, diarrhea, allergy, inflammation in eastern Asian countries. 2,3) Main chemical components of S. flavescens include flavonoids (1.5%), alkaloids (3.3%), alkylxanthones, quinones, triterpene glycosides, fatty acids as well as essential oils and recently, several clinical studies reported that alkaloids of S. flavescens were efficacious in treating various types of solid tumors (including breast, lung, liver and gastrointestinal tract cancers), which drew close attention to this traditional herbal plant.…”
Section: Sophora Flavescens Aiton Kuraramentioning
confidence: 99%
“…1,4) In 1889, the characteristic compound matrine was isolated from the dry roots of S. flavescens by Nagai 5) and then in 1966, Okuda et al confirmed the absolute structure of (+)-matrine.…”
mentioning
confidence: 99%